Quantitative multi-element analysis of Argonne Premium Coal samples by ETV-ICP OES – A highly efficient direct analytical technique for inorganics in coal. (15th July 2015) - Vogt, Thomas; Bauer, Daniela; Neuroth, Markus; Otto, Matthias
Graphical abstract: Highlights: A novel direct solid sampling method for coal analysis was developed. Simultaneous quantitative multi-element analysis of major and trace elements. No need for any further sample pretreatment. Element release in dependence on temperature can be determined by ETV-ICP OES. The possibility of element speciation as result of release temperature is shown. Abstract: A new and highly efficient solid sampling method was developed for fast direct multi-element analysis in coals using electrothermal vaporization as sample introduction system for inductively coupled plasma optical emission spectrometry (ETV-ICP OES). With ETV coupled to ICP OES it is possible to analyze trace and major elements simultaneously in whole coal samples with a minimum effort of sample preparation and short analyzing times. The quantitative determination of Al, Ba, Ca, Cr, Cu, Fe, K, Mg, Mn, Na, Ni, P, Pb, S, Si, Ti, V and Zn by ETV-ICP OES in all eight Argonne Premium Coals, covering the rank range from lignite to semi-anthracite, is presented. The results are comparable with the reported element contents in literature. It is shown, that the fast direct solid sampling multi-element spectroscopic method, based on electrothermal vaporization of powdered samples, is proved to be a suitable alternative to labor intensive traditional methods.